Mitochondrial disorders: aetiologies, models systems, and candidate therapies - Chadderton, Naomi; Kenna, Paul; Millington-Ward, Sophia; Farrar, Gwyneth (My University, 2013)
It has become evident that many human disorders are characterised by mitochondrial dysfunction either at a primary level, due to mutations in genes whose encoded products are involved in oxidative phosphorylation, or at a secondary level, due to the accumulation of mitochondrial DNA (mtDNA) mutations. This has prompted keen interest in the development of cell and animal models and in exploring innovative therapeutic strategies to modulate the mitochondrial deficiencies observed in these diseases. Key advances in these areas are outlined in this review, with a focus on Leber hereditary optic neuropathy (LHON). This exciting field is set to grow exponentially and yield many candidate therapies to treat this class of disease.
PUBLISHED
Keywords: gene therapy; Leber hereditary optic neuropathy; mitochondrial disease; gene therapy; Leber hereditary optic neuropathy; mitochondrial disease